Soil Exploitation and Environmental Impacts of Brick Making in Wasur 2 Merauke Regency - Zegovia Parera (Jurnal Hukum Volkgeist, 2021)
Merauke Regency is a coastal area with muddy soil conditions. sand and gravel materials, because of these conditions the community and housing business actors use red bricks as material for development in Merauke district which is currently being carried out in all sectors of life, especially building and housing construction.